2007
DOI: 10.1061/(asce)0733-9399(2007)133:10(1086)
|View full text |Cite
|
Sign up to set email alerts
|

Ocean Currents-Induced Pipeline Lateral Stability on Sandy Seabed

Abstract: Unlike previous mechanical actuator loading methods, in this study, a hydrodynamic loading method was employed in a flow flume for simulating ocean currents induced submarine pipeline stability on a sandy seabed. It has been observed that, in the process of pipeline losing lateral stability in currents, there usually exist three characteristic times: ͑1͒ onset of sand scour; ͑2͒ slight lateral displacement of pipeline; and ͑3͒ breakout of pipeline. An empirical linear relationship is established between the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 14 publications
1
15
0
Order By: Relevance
“…Based on experiments with a sandy bed, Gao et al (2007) describes the behavior of a slightly embedded 1036 pipe, which loses its lateral stability as a result of continuously increasing action by current or waves. In the 1037 current-alone case, the pipe initially pushes the nearby soil ahead with an associated slight lateral pipe 1038 displacement, until it at a certain time loses its stability and breaks out with a resulting large displacement 1039 in the current direction.…”
mentioning
confidence: 99%
“…Based on experiments with a sandy bed, Gao et al (2007) describes the behavior of a slightly embedded 1036 pipe, which loses its lateral stability as a result of continuously increasing action by current or waves. In the 1037 current-alone case, the pipe initially pushes the nearby soil ahead with an associated slight lateral pipe 1038 displacement, until it at a certain time loses its stability and breaks out with a resulting large displacement 1039 in the current direction.…”
mentioning
confidence: 99%
“…is the kinematic viscosity of the water) could not be satisfied concurrently with those of the Froude number and the Keulegan-Carpenter number, the values of Re for the models and that for the prototypes should be approximately within the same regime (e.g., the subcritical or supercritical regimes) to ensure similar flow features around the pipeline. Based on the similarity analyses and the physical modeling experiments under the wave and current loading conditions, respectively [15,16] , it was found that the controlling non-dimensional parameter of hydrodynamics for the pipeline lateral instability is the Froude number ( ) Fr , and another controlling parameter is the non-dimensional submerged weight of the pipelines , indicating that the pipes are more stable in currents than in waves due to the inertia effect of wave movements. Note that the above recommended values for the two parameters a and b are based on the results of model tests on a uniform medium sand-bed (the mean diameter of sand particles 50 = 0.38 mm d ).…”
Section: Flow-pipe-soil Couplingmentioning
confidence: 99%
“…Although the pipe on-bottom stability in currents seems less complex than in waves, till now, the underlying physical mechanism has not been well revealed [1].…”
Section: Omae2010-20183mentioning
confidence: 99%
“…The submarine pipeline on-bottom stability in the severe ocean environments involves the "flow-pipe-soil" interaction [1]. To avoid the occurrence of pipeline on-bottom instability, i.e.…”
Section: Introductionmentioning
confidence: 99%